Synchronous malignant rhabdoid tumor of the kidney and adrenal neuroblastoma in an infant treated with proton beam therapy: a case report and literature review - Han, Wei; Teng, Huaida; Shi, Junlei; Zhang, Nan; Tumendemberel, Jargal; Lu, Ping; Wang, Jie; Zheng, Jie; Liu, Xinan; Meng, Deguang; Shimizu, Shosei (Frontiers in Oncology, 2026)
This case report and literature review presents a 4-month-old infant with a synchronous malignant rhabdoid tumor of the kidney and adrenal neuroblastoma, an exceptionally rare combination without established treatment guidelines. Following surgical resection, proton beam therapy (14 Gy in 10 fractions) was administered to the abdominal–pelvic tumor bed with stringent organ-sparing objectives. Contemporary literature supports proton beam therapy’s (PBT’s) dosimetric advantages for organ preservation in pediatric abdominal malignancies. At 1-year follow-up, the patient remained disease-free, with preserved renal function and normal skeletal development, supporting PBT’s role in minimizing late effects while achieving local control in infant malignancies when conventional photon radiotherapy would pose substantial developmental risks.